Funding opportunities for affordable housing programme - Maina, Peter Wanyoike (Strathmore University, 2021)
The purpose of this research paper is to examine the funding opportunities available for the affordable housing program. The study looks at the current channels of funding, the challenges facing affordable housing, the role of the private and goverm11ent sector. Primary data used was collected through presenting questionnaires to respondents in different financial sectors and there was a 64% response rate. The basis used for data collection were looking for the current funding opportunities, the difference between the funding opportunities in affordable housing than in other housing development, the drawbacks in funding and how can the funding opportunities be optimized. The data collected was input into Ms Excel and expressed as pie chart to make more meaning. The results show that there is need for encouragement of saving and contribution towards home ownership by the general public as this will be a catalyst in achievement of affordable housing. We find that state contribution is the best funding source for the affordable housing program and that government funding will still go back to the individual tenants and private entities through the housing tax levy
Submitted in partial fulfillment of the requirements for the Degree of Bachelor of Business Science at Strathmore University